PERNIKAHAN DINI DAN PROBLEMATIKANYA PADA MASA PANDEMI COVID-19 - Reza Hilmy Luayyin (JAS : Jurnal Ahwal Syakhshiyyah, 2021)
This research was motivated by the information on the number of people who had early marriages at KUA Sumberasih or marriages under the age of 19. Even though currently Indonesia is experiencing a pandemic of Covid -19. Even up to one day there can be eight weddings at once in the Gili area of Ketapang Village, Sumberasih, Probolinggo. The purpose of this study was to determine the factors that influence the occurrence of early marriage during the Covid-19 pandemic. In this study, the authors used a qualitative descriptive method. Qualitative descriptive method is a method that aims to describe the nature of something that is taking place at the time the research is carried out and examine the causes of a symptom. The data collection technique obtained by the writer through observation and interview techniques to KUA Sumberasih. The results of this study found data that during the pandemic period from March to December 2020 as many as 15 people had do early marriages, it can be seen through the data of KUA Sumberasih through the determination of the dispensation of marriage submitted to the religious court. From the basic data, it is found that there are two things behind the occurrence of early marriage during the pandemic, it is outside pregnancy of legal marriage and also to avoid both of relationship. The problems found by early marriage couples after early marriage include three things, it is Â problems for the early marriage couple itself, the problems for the child of the early marriage partner, and the problems for both parents of early spouses.Keywords : Early Marriage, Problematic, Pandemic